Die Schuldenbremse als politisches Projekt - Eicker-Wolf, Kai; Himpele, Klemens (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
The German constitution has rules concerning public debt, and those rules changed a couple of years ago. Starting in 2016, new public debts are permitted up to a level of 0.35 percent of GDP for the German federation. The German states are not allowed net new borrowing at all, starting in 2020. This is a crucial change, given the old constitutional law, which allows debts for public investments. The following article deals with the question of whether the new law is used to „starve the beast”, in other words: to cutback public activities and authorise tax reductions. The article interprets the new dept regulations as a political project rather than an economical imperative.